Fiber Bragg grating sensor-based monitoring strategy for slope deformation in centrifugal model test. Issue 1 (17th April 2018) - Guo, Yongxing; Fu, Jianjun; Li, Longqi; Xiong, Li
Abstract : Purpose: Centrifugal model tests can accelerate the characterization of landslides and demonstrate the form of slope failure, which is an important measure to research its instability mechanisms. Simply observing the slope landslide before and after a centrifugal model test cannot reveal the processes involved in real-time deformation. Electromagnetic sensors have severed as an existing method for real-time measurement, however, this approach has significant challenges, including poor signal quality, interference, and complex implementation and wiring schemes. This paper aims to overcome the shortcomings of the existing measurement methods. Design/methodology/approach: This work uses the advantages of fiber Bragg grating (FBG) sensors with their small form-factor and potential for series multiplexing in a single fiber to demonstrate a monitoring strategy for model centrifugal tests. A slope surface deformation displacement sensor, FBG anchor sensor and FBG anti-slide piling sensor have been designed. These sensors are installed in the slope models, while centrifugal acceleration tests under 100 g are carried out. Findings: FBG sensors obtain three types of deformation information, demonstrating the feasibility and validity of this measurement strategy. Originality/value: The experimental results provide important details about instability mechanisms of a slope, which has great significance in research on slope model monitoring techniques and slope stability.